THE FUNCTIONS OF TALES AND THE VALUE IN RESPECT OF TEACHING GHARĀVĀSA-DHAMMA DOCTRINES IN NITHAN SIKHAO, COLLECTION OF LIFE-DEVELOPMENT TALES BY ART-ONG JUMSAI NA AYUDHYA - Khunmathurot, Songphop (Journal of Education and Innovation, 2023)
The objective of this research is to study the functions of tales and the value in respect of teaching Gharāvāsa-dhamma doctrines in Nithan Sikhao, Collection of Life-Development Tales 1-4 by Art-ong Jumsai Na Ayudhya. The research was conducted with the documentary research method. The data analysis was done with the open coding technique, and the research results were presented in the style of analytical description. As regards the research results, it was found that Nithan Sikhao, Collection of Life-Development Tales by Art-ong Jumsai Na Ayudhya is young people’s literature with functions in accordance with William Bascom’s functionalism. The function of maintaining the behavioral traditions of people in society is of the greatest proportion. It is followed by the functions of reflecting society, teaching and entertaining sequentially. Furthermore, as regards the value in respect of teaching the Gharāvāsa-dhamma doctrines, it was found that the teaching on Cāga was of the greatest proportion. It is followed by the teaching of Sacca, Dama, and Khanti sequentially. These are the dhammic doctrines for laypeople, the dhammic doctrines of conduct for the ordinary people in society. Therefore, these tales allow child and juvenile readers to receive some ideas and morals and ethics to be guidelines for living, which is a method of implantation to make children and youth grow up to become people with good quality of life through writings in the tale genre.